Developing a South African services agenda : case study of the mining services sector - Mtshali, Sithembile Nokwazi (GSB: Faculty, 2016)
The services sector accounts for approximately 70% of South Africa's gross domestic product (GDP) and has emerged as one of South Africa's key exports with regional and global destinations. The sector is also a key provider of employment registering just above 8.5 million jobs in March 2014, according to Statistics South Africa. It is for this reason that the sector has been earmarked to give the required impetus to realise the export driven growth, which underpins the current government strategy for economic development and growth. Using the mining services sector, as a case study, this study highlights the importance of services, as an important input to operating costs in the production and manufacturing sectors. It further highlights the importance of services in determining the competitiveness of the manufacturing and production sectors, through effective sourcing and more importantly availability. This is done in the context of the growing African market, especially the mining sector and the opportunities presented by new mineral discoveries in Africa. This study is presented to support the development of a strategic and comprehensive trade strategy for services. Tracking the development of South Africa's trade policy, the rationale for the different positions that have been taken by government are presented to illustrate how government has used trade policy as a tool to advance its objectives at varying stages of South Africa's economic development. The study thereafter undertakes an analysis of the current trade policy to better understand how government view the role that is to be played by trade policy in supporting economic development. This analysis identifies gaps within the current trade policy in terms of the role that trade policy ought to play.